COMPARISON OF THE MAMDANI AND SUGENO METHOD TO INCREASE THE LEVEL OFANALYSIS THE ADVANTAGES OF INFRASTRUCTURE DEVELOPMENT - Ertina Sabarita Barus (INFOKUM, 2021)
To increase the accuracy of the output value of a Mamdani-based decision support system compared to the manual analysis system. The value of the analysis carried out using the system should have a value close to the value that is done manually. For this reason, this study will compare Mamdani and Sugeno methods to observe the similarity of values with manual calculation data. In processing fuzzy input data produces output from the inference process which is then classified in 5 feasibility conditions, namely, low, normal, high, very high and not feasible which is used as a supporting facility in making infrastructure development decisions in an area